Discovery of a highly efficient TylF methyltransferase via random mutagenesis for improving tylosin production - Fan, Jingyan; Yao, Zhiming; Yan, Chaoyue; Hao, Meilin; Dai, Jun; Zou, Wenjin; Ni, Minghui; Li, Tingting; Li, Lu; Li, Shuo; Liu, Jie; Huang, Qi; et al. (Computational and structural biotechnology journal, 2023)
Macrolides are currently a class of extensively used antibiotics in human and animal medicine. Tylosin is not only one of the most important veterinary macrolides but also an indispensable material for the bio- and chemo-synthesis of new generations of macrolide antibiotics. Thus, improving its production yield is of great value. As the key rate-limiting enzyme catalyzing the terminal step of tylosin biosynthesis in Streptomyces fradiae (S. fradiae), TylF methyltransferase’s catalytic activity directly affects tylosin yield. In this study, a tylF mutant library of S. fradiae SF-3 was constructed based on error-prone PCR technology. After two steps of screening in 24-well plates and conical flask fermentation and enzyme activity assay, a mutant strain was identified with higher TylF activity and tylosin yield. The mutation of tyrosine to phenylalanine is localized at the 139th amino acid residue on TylF (TylFY139F), and protein structure simulations demonstrated that this mutation changed the protein structure of TylF. Compared with wild-type protein TylF, TylFY139F exhibited higher enzymatic activity and thermostability. More importantly, the Y139 residue in TylF is a previously unidentified position required for TylF activity and tylosin production in S. fradiae, indicating the further potential to engineer the enzyme. These findings provide helpful information for the directed molecular evolution of this important enzyme and the genetic modification of tylosin-producing bacteria. [Display omitted]